Electric control of magnetic exchange in a molecular spin triangle - Cini, Alberto; Böhme, Michael; Kintzel, Benjamin; Perfetti, Mauro; Plass, Winfried; Sessoli, Roberta; Fittipaldi, Maria (Nature communications, 2025)
Spin-electric effects are crucial for quantum technologies, offering several advantages over standard magnetic field-based spin control. Seeking a mechanism independent of spin-orbit interaction, here we report the detection of a spin-electric effect in the [Cu 3 (saltag)(py) 6 ]ClO 4 spin triangle. The effect is investigated by electron paramagnetic resonance under electric field modulation on single crystals. The anisotropy of the magnetic response to the electric field is addressed, and comprehensive ab initio calculations are performed to elucidate its origin. We demonstrate that when the electric field is applied in the plane of the triangle, the dominant contribution to the observed spin-electric signal arises from a variation of the isotropic exchange interaction. Our combined theoretical and experimental approach demonstrates that, in our system, there is no evidence of antisymmetric exchange (Dzyaloshinskii-Moriya) interaction, confirming that electric-field control of magnetic exchange is achievable in the absence of significant spin–orbit coupling. Moreover, we underscore the crucial role of the bridging ligand, which opens new avenues for chemically optimizing spin–electric coupling. Electric control of magnetic interactions in a molecular spin-frustrated triangle is demonstrated through experiments and supported by ab initio calculations. This result opens new pathways for scalability by local control of qubit–qubit coupling.